PENDIDIKAN KARAKTER DALAM PEMBELAJARAN IPS DI SMP NEGERI 4 ALALAK BARITO KUALA - Nurmiati Nurmiati (Universitas Lambung Mangkurat, 2015)
The purposesof this study are (1) to describe the plan of the character education in the teaching and learning of IPS at SMP Negeri 4 Alalak Barito Kuala, (2) to describe the implementation of character education in SMP Negeri 4 Alalak Barito Kuala, and (3) to describe how the evaluation is carried out in the teaching and learning of IPS at SMP Negeri 4 Alalak.This research was conducted at SMP 4 Alalak Barito Kuala. It appliesqualitative methods withtechniques of data collection that include observation, documentation, and interviews (purposive sampling).The analysis covers the data reduction, presentation of data and conclusion drawing. The data validity testingwas done by trianggulation and peerinspection.The results of this study show that (1) the plan of character education in the teaching and learning of IPS at SMP 4 Alalak Barito Kuala was done by preparing the syillabus and lesson plans in advance, (2) the impletation of the character education in the teaching and learning of IPS at SMP 4 Alalak Barito Kuala is by means of working in group, examining particularly the story of the hero characters, performing a drama, and (3) the evaluation of the character education in the teaching and learning of IPS at SMP Negeri 4 Alalak Barito Kuala is through the evaluation of the syillabus and lesson plans as well as evaluating the final result of the students’ attitude changes inobeying the school rules.Keywords: character education, teaching and learning of IPS